G.R.H. Wright and the Restoration of Ancient Monuments - Balderstone, Susan (Buried History: The Journal of the Australian Institute of Archaeology, 2018)
G.R.H. Wright worked in the Middle East and India on the restoration of ancient monuments during a period when principles for conservation and restoration practice established in Europe following the Second World War began to evolve to accommodate the needs of fast-developing Asia. The paper describes his experience as he learned on the job in the Middle East and tried to forge his way through the cultural complexities in India providing an early illustration of the issues that have come to the fore in recent years regarding authenticity as it relates to reconstruction.